All's fair in love, war, and high school - Rallison, Janette, 1966- (New York : Scholastic, 2003)
When head cheerleader Samantha Taylor does poorly on the SAT exam, she determines that her only hope for college admission is to win the election for student body president, but her razor wit and acid tongue make her better suited to dishing out insults than winning votes.
Keywords: High schools -- Fiction; Schools -- Fiction; Self-perception -- Fiction; Elections -- Fiction